Bacteriological Profile and Antibiotic Susceptibility Pattern of Isolates from Suspected Neonatal Septicemia Patients in Different Hospitals of Chattogram (IAHS Medical Journal, 2024)
Background: Bacterial blood stream infection is an important cause of morbidity and mortality in neonates. This study was undertaken to identify the bacterial isolates from suspected neonatal septicemia patients and to understand their antimicrobial susceptibility pattern in Chattogram.Materials and methods: A cross-sectional descriptive type of study was done for a period of two years from January 2022 to December 2023. Blood samples from 340 neonates with clinically suspected septicemia were taken for automated culture and susceptibility test was conducted in Bacteriology Laboratory of IbneSina, Chattogram. The samples were collected and processed following standard microbiological techniques and an antibiotic susceptibility test was done on pure culture isolates using disc-diffusion method for the commonly used antibiotics. The data were analyzed by using SPSS version 20 and the results were summarized by using tables and graphs.Results: Out of 340 blood culture done, 62 (18.24%) were positive. Among them 61.3% were of early onset sepsis. The predominant bacteria isolated was Klebsiella spp. 27 (43.6%) followed by Coagulase negative staphylococci 12(19.4%), Salmonella typhi 10 (16.1%), E. coli 6 (9.6%) and Pseudomonas 5 (8.0%). Antibiotic susceptibility tests showed that the most sensitive antibiotics to Gram-negative organisms wereImipenem (81-100%), Tazobactam-Piperacillin (74-100%), Amikacin (67-90%), Ceftriaxone (60-100%) and Levofloxacin (63-80%). Maximum resistanceamong Gram-negative organisms were seen in Ampicillin (60-100%), Cotrimoxazole (60-100%) and Cefixime (30-80%). Among Gram-positive organisms, all strains (100%) were sensitive to Linezolid and Vancomycin. Other alternates with good sensitivity were Amikacin (92%), Imipenem (83%), Ceftriaxone (83%) and Levofloxacin (75%). While maximum resistance was seen to Ampicillin (83%), Amoxiclav (75%), Cefixime (75%) and Ciprofloxacin (75%).Conclusions: In the present study, most of the pathogens isolated from blood cultures were Gram negative and they showed high resistance to commonly used antibiotics. Therefore, rational use of antibiotics after sensitivity testing should be practiced.IAHS Medical Journal Vol 7(1), June 2024; 68-73